Pendeteksian potensi kawasan RTH menggunakan citra satelit landsat 8 - Respati Wikantiyoso; Aditya Galih Sulaksono; Tonny Suhartono (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Green city development policies have an essential role in improving the ecological functions of a municipality. According to Law 26/2007 on spatial planning, it contains provinsions for green open space which oblige the government to set aside 30% of the city as green open space. However, the main obstacle in providing green open space remains the limited availability of urban land. Therefore, efforts are needed to detect urban land that is available for use as green open space. The purpose of this study is to determine the initial description of the availability of green open space in Malang City. This study uses an integrated method of calculating the Normalized Difference Vegetation Index (NDVI) with land cover classification. NDVI analysis reveals the distribution value of vegetation density in Malang City. Based on NDVI analysis results, green open space requires medium and high density vegetation. In Malang City, only 2946.56 ha, or 26.60% of the city, meets these requirements. The availability of green open space in Malang City therefore does not meet minimum green open space requirements. This study's results suggest the need for additional policies aimed at providing green open space for Malang City.